2013
DOI: 10.5812/ijhrba.10791
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Training Acceptance/Commitment and Training Emotion Regulation on High-Risk Behaviors of Students with Dyscalculia

Abstract: BackgroundNow a days the utilization of Acceptance / Commitment and Emotion Regulation Strategy as a comprehensive treatment plan has been discussed in both the prevention and the control of destructive and risky behaviors. Treatment based on Acceptance/Commitment and Emotion Regulation was effective in both the improvement and the control of high-risk behaviors of students with dyscalculia.ObjectivesThe purpose of this study was to investigate the effectiveness of Acceptance and Commitment, and Emotional Regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…However, other studies have shown the effectiveness of different approaches. For example, Narimani et al showed that acceptance or commitment and emotion regulation training were effective in reducing high-risk behaviors of students with dyscalculia ( 34 ). Another study conducted by Martin and Dahlen (2005) shows an association between cognitive ER and depression, anxiety, stress and anger ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown the effectiveness of different approaches. For example, Narimani et al showed that acceptance or commitment and emotion regulation training were effective in reducing high-risk behaviors of students with dyscalculia ( 34 ). Another study conducted by Martin and Dahlen (2005) shows an association between cognitive ER and depression, anxiety, stress and anger ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This inability can disturb their organization of cognitions and emotions ( 6 ). These children, usually because of the lack of sincere relationships and enough stable emotional connection to their parents, unawareness of their parents’ emotions, and inability in cognitive processing of their feelings, are unable to identify, perceive, and describe their own emotions, and have limited capability in adapting to stressing situations ( 5 ). One of the methods of controlling stress, especially about emotions, is discharging them.…”
Section: Discussionmentioning
confidence: 99%
“…To explain these findings, we can say that individuals with low scores in alexithymia, have more mental abilities to process social information. This ability can help them to have a better perception of negative and harmful consequences of substance abuse, cigarette smoking, alcohol consumption, and other high-risk behaviors, and thus, be more successful to resist against mental and social stresses pushing them to high-risk behaviors ( 5 ). In fact, they can enhance their social relationships by accurate formulation and process of information and distinguish having right or wrong behaviors in different situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a preliminary study on 40 students, Lotfi, Abolghasemi, & Narimani, (2014) reported -0.54 as the correlation coefficient of EPS with the emotion regulation scale of α=0.01. Cronbach's alpha coefficient of this inventory was calculated as 0.95 in another study (Narimani, 2013).…”
Section: Methodsmentioning
confidence: 99%